Socioeconomic Determinants of Income Inequality in Nigeria and Their Implications for Economic Growth - Vivian C. Onyejegbu; Emilia Mukaosolu Mgbemena (Paspama Institute, 2026)
The persistent challenge of income inequality and uneven growth in Nigeria continues to hinder sustainable development efforts. The study examined the determinants of income inequality and economic growth in Nigeria (1994–2023) was conducted to (i) examine the impact of access to education, healthcare, and unemployment on income inequality on economic growth in Nigeria. The study employed the Autoregressive Distributed Lag (ARDL) model with the Fully Modified Ordinary Least Squares (FMOLS) as a robustness check after conducting necessary diagnostic tests. The core variables include income inequality, economic growth, secondary school enrolment, life expectancy, maternal mortality rate, unemployment, government recurrent education and health expenditures, institutional quality index, FDI, inflation, oil price, and trade openness. Findings from the first model show that secondary school enrolment significantly increased income inequality (0.3394; p < 0.05), while life expectancy reduced it (-3.5144; p < 0.01); unemployment had a negative and significant impact (-12.9941; p < 0.01), implying that improved employment and healthcare reduce inequality in the long run. However, they all have a significant impact, with only unemployment having a negative impact. Furthermore, in the short run, only FDI enhances growth, whereas inflation and the institutional quality index are the only two factors that constrain growth. Based on these results, the study recommends enhanced investment in quality education and healthcare, job creation through fiscal decentralization, and institutional reforms to stabilize inflation and attract productive FDI. Furthermore, progressive taxation and social protection mechanisms are advocated to promote inclusive and equitable growth. Overall, the study concludes that reducing structural inequalities through human capital development and strong institutional frameworks is indispensable for achieving sustainable economic growth in Nigeria.